Physiological Parameters of Latex from Controlled Upward Tapping of Hevea Brasiliensis Stimulated With Ethephon - Nguyen, Anh Nghia (1997)

(untitled)
A study was carried out to evaluate the effect of several ethephon concentrations (5%, 10% and 20%) on yield and some physiological parameters of latex obtained from Controlled Upward Tapping (CUT) of clone RRlM 600. The relationships between yield, physiological parameters and their interactions were investigated. A good response t o stimulation on yield was observed. The yields in stimulated treatments were from 192.5% to 267.7% of control over the time of the study.